The “Marriage Is Scary” Phenomenon on Social Media: An Existential Feminist Perspective - Khasanah, Faidatul Nur; Ma'mun, Sukron (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
The “Marriage is Scary” phenomenon, which has gained prominence on social media platforms such as TikTok and X (formerly Twitter), reflects the concerns of the younger generation, particularly women, regarding the institution of marriage. This expression has emerged as a form of resistance against social constructs that pressure women to marry at a certain age, often without regard for emotional, financial, or existential readiness. This article analyses the “Marriage is Scary” phenomenon through the lens of Simone de Beauvoir’s existentialist feminism. Within Beauvoir’s theoretical framework, women are frequently positioned as the other and confined to roles of immanence, which restrict their freedom and capacity for transcendence. Employing a literature-based approach combined with social media content analysis, this study demonstrates that the “Marriage is Scary” narrative reflects women’s growing awareness of their right to freedom of choice and their pursuit of authentic existence. The findings suggest that this phenomenon signifies a broader paradigm shift, from perceiving marriage as a social obligation to viewing it as a conscious, autonomous decision. Ultimately, “Marriage is Scary” is not merely a fleeting online trend but a symbolic expression of women’s ongoing struggle to reclaim autonomy and freedom within patriarchal social structures.